The bone code [large type] - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series., 2021)
"On the way to Isle of Palms off the South Carolina coast, Tempe receives a call about two decomposed bodies wrapped in plastic sheeting and bound with electrical wire. The details are identical to those of an unsolved case Tempe handled in Quebec years earlier. She travels to Montreal to gather evidence, while health authorities in South Carolina become increasingly alarmed as a flesh-eating contagion spreads. So focused is Tempe on identifying the container victims that, initially, she doesn't register how their murders and the pestilence may be related. But someone is protecting a dark secret--and willing to do anything to keep it hidden"--Page 4 of cover.